PENAFSIRAN PEMBERIAN DISPENSASI PERKAWINAN DI BAWAH UMUR DI PENGADILAN AGAMA KABUPATEN SUKOHARJO TAHUN 2019 - 2021 - Munawir, M; Wibowo, Muhammad Kurniawan Budi; Baehaqi, B (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
Interpretation is a method of legal interpretation that provides an easy-to-understand explanation of the text of the law so that the scope of the rule can be determined in relation to certain events. Judge's interpretation or interpretation is one of the processes that must be taken by the court in order to obtain certainty regarding the meaning of statutory law. Marriage dispensation is an exception to the rule or law that is given to applicants to get married but are not old enough in accordance with the terms and conditions of the applicable law. The author in this study used a qualitative descriptive method, the data collection method is original data from the Religious Courts of Sukoharjo Regency, both about annual reports and direct interviews from existing judges in dealing with the problem of interpreting the dispensation of underage marriages. The data was then analyzed descriptively qualitatively, namely to describe what was happening at that time. To test the validity of the data is done through Editing and Classifying. The results of the study show that the interpretation of the granting of underage marriage dispensation in Sukoharjo Regency in 2019-2021 is carried out by submitting a marriage dispensation application stating that the marriage must still be carried out due to an urgent and emergency situation that must be married or handled immediately. The factors that led to the interpretation of the granting of dispensation for underage marriages, namely pregnancy out of wedlock, parental factors, educational factors, economic factors and of course the Covid 19 factor in 2020 which stopped all forms of human activity or what are known to be restrictions within the scope all sectors of human life.